Rancang Bangun Mesin Pemipil Jagung Dua Silinder menggunakan Motor Listrik - Sai'in, Ali; Saputra, Eko; Nugroho, Wahyu Isti; Hardian, Rudino Tuqo (Jurnal Rekayasa Mesin, 2021)
Seeing the situation of animal feed needs which tend to increase every year, it must be accompanied by the procurement of production machines to reduce the productivity of corn. Corn sheller machine is a tool that serves to release corn kernels from the cob. Along with technological developments that continue to progress, many production machines have sprung up such as corn shellers ranging from those that are operated manually to automatic. Each machine has different advantages and disadvantages. In the design of this corn sheller machine the main driver uses an electric motor. The design of this corn sheller machine aims to help ease the burden on corn farmers in particular. At first the corn shelling was done manually, then it developed using a large selep machine but the costs incurred were relatively expensive. The design of a two-cylinder corn sheller machine uses an electric motor to determine the appropriate design and construction of the corn sheller machine. In this machine there is no corn diameter limit for the shelling process in other words this machine is designed for all sizes of corn. In this design using several stages, namely first planning the design of the engine frame, electric motor, pulley and v-belt ratio and the calculation of the shaft. The result of the design is a machine design that is 1200 mm long, 1200 mm wide and 800 mm high. The sheller machine is driven using an electric motor of 500 watts, Rpm 1400 with a transmission system using a pulley and a v-belt ratio of 1: 1. There is no limit to the diameter of corn kernels in the shelling process using this machine. So it can be concluded that this machine has an effective design and sufficient shelling results, able to reduce post-harvest costs for corn farmers.